Mormon women's history : beyond biography - Cope, Rachel (Fairleigh Dickinson University Press Mormon studies series., 2017)
Mormon Women's History: Beyond Biography demonstrates that the history and experience of Mormon women is central to the history of Mormonism and to histories of American religion, politics, and culture.